In vitro metabolism of 25-hydroxyvitamin D(3) by isolated rat kidney cells - Turner, Russell T. (1980)
Cells were dispersed from rat kidney after enzymatic digestion of the extracellular matrix. When the cells were suspended in a serum-free medium and incubated with (3)H-labeled 25-hydroxyvitamin D(3) (25-OH-D(3)) several polar metabolites, including 1,25-(OH)(2)[(3)H]D(3) and 24,25-(OH)(2)[(3)H]D(3) were produced. The specific activities of the 25-OH-D(3):1- and 24-hydroxylases in isolated rat kidney cells were 10-100 times greater than in avian kidney homogenates. The rates of production of 1,25-(OH)(2)D(3) and 24,25-(OH)(2)D(3) were linear over a wide range in cell densities (0.65-5.0 × 10(6) cells per ml) and substrate concentrations (3.5-70 nM). The rate of production of 24,25-(OH)(2)[(3)H]D(3) from 25-OH-[(3)H]D(3) by cells isolated from rats fed control diet was linear with time for up to 30 min, while the synthesis of 1,25-(OH)(2)[(3)H]D(3) was linear for over 90 min. The specific activity of the 25-OH-D(3):1-hydroxylase was increased in kidney cells from vitamin D-deficient rats (11.5 fmol/min per 10(6) cells) as well as calcium-deficient rats (8.1 fmol/min per 10(6) cells) when compared to cells from rats fed the control diet (2.0 fmol/min per 10(6) cells). Also, the specific activity of the 25-OH-D(3):24-hydroxylase was reduced in cells from the vitamin D-deficient rats (<0.2 fmol/min per 10(6) cells) and calcium-deficient rats (5.1 fmol/min per 10(6) cells) compared to the controls (15.2 fmol/min per 10(6) cells). On the basis of these results, as well as previous in vivo studies, we conclude that the metabolism of 25-OH-D(3) by freshly isolated rat kidney cells reflects the in vivo activities of the renal vitamin D-metabolizing enzymes and may prove useful as an assay.